Hypoglycaemic effect of Stigmast-4-en-3-one, from Parkia speciosa empty pods - Jamaluddin, Fathaiya; Mohamed, Suhaila; Lajis, Md.Nordin (Elsevier, 1995)
Oral administration of the chloroform extracts of Parkia speciosa (petai papan) empty pods to alloxan-induced diabetic rats produced a significant reduction in blood glucose levels. A hypoglycaemic assay guided extraction, isolation and structure elucidation gave stigmast-4-en-3-one. Stigmast-4-en-3-one produced 84% activity at 100 mg kg-1 body weight (BW) compared to 111% activity of glibenclamide at 5 mg kg-1 BW dosages. The minimum effective dose which produced statistically significant hypoglycaemic effect was 50 mg pericarp kg-1 BW. Hypoglycaemic effect was not observed in healthy rats. Stigmast-4-en-3-one is therefore identified as a new oral hypoglycaemic agent occurring naturally in food.